Innovating product design through university-industry collaboration: Codesigning a bushfire rated skylight. (September 2021) - Paay, Jeni; Kuys, Blair; Taffe, Simone
Abstract : Innovation is important for improving products for long-term business success. However, small-to-medium enterprises don't always have time to innovate. SMEs benefit from university-industry collaborations, where design researchers contribute knowledge and time to help them innovate product design and manufacturing processes. Using codesign to generate innovative design solutions in the collaboration provides engagement and ensures everyone is encouraged to share their viewpoints and expertise. Design thinking adds a communication conduit, encouraging exploration and evaluation of alternative ideas. To illustrate the success of integrating codesign with design thinking in university-industry collaboration, we present a case study of designing an award-winning innovative skylight. The collaborative outcome evidences the value in the partnership by advancing university knowledge and increasing company productivity. Highlights: Integrating codesign and design thinking to facilitate successful University-Industry collaboration for design innovation. Using codesign to advance communication between product design research and practice. Using design thinking communication conduits of seeing, knowing, thinking, acting and reflecting to innovate. A case study illustrating mutual benefits and challenges in university-industry collaboration. Evidence of success of approach through three times Design Award winning innovative product outcome.